X-law operation for energy-efficient time-of-arrival positioning to achieve higher accuracy with lower bandwidth: A game-changer for UWB localization devices - Mohammad Esmaeili-Yadaki; Hassan Khani (ICT Express)
Ultra-wideband (UWB) technology is a good candidate for low-latency high-resolution localization. This paper proposes the x-law operation (XLO) to boost the positioning accuracy of UWB localization systems. The proposed scheme significantly reduces the contribution of low-SNR samples and increases the time resolution of the pulse. Thus, the XLO achieves a time-of-arrival (ToA) positioning accuracy that existing methods require more energy and bandwidth to attain. The significant performance gain of the XLO for localization makes the XLO a good candidate for simultaneous positioning and communication with low complexity, high performance, and low power consumption suited for Internet of Things (IoT) devices.